Determinant of economic growth in asean countries 2015-2022 - Muh Irwin; Rahmatia Yunus; Sanusi Fattah; Nur Dwiana Sari Saudi (Association Of Indonesian Entrepreneurship Study Programs, 2024)
The aim of this research is to see the influence of macroeconomic variables on the GDP of ASEAN countries. This research uses data for the past 7 years from 2015-2022 and uses market analysis to discuss labor force levels and income levels in ASEAN countries. Using a two-stage least squares simultaneous equation model. The data taken is Gross Domestic Product, Labor Force and Exchange Rates. Based on the test results, it shows that the variables that have an influence on GDP are the Labor Force, Inflation, while the Exchange Rate has no influence on GDP.